Effects of qigong exercise on cardiovascular risk factors in patients with metabolic syndrome: A systematic review and meta-analysis - Tao, Shuoxiu; Li, Zaimin (Frontiers in Physiology, 2023)
Background: As a traditional Chinese exercise system, Qigong includes many types of exercises, including Baduanjin, Wuqinxi, Yijinjing, and Liuzijue. However, reviews highlighting the effects of a specific type of Qigong exercise in patients with metabolic syndrome or risk factors for metabolic syndrome are limited, and no articles have systematically evaluated the effects of Qigong exercise on cardiovascular risk factors in patients with metabolic syndrome. Therefore, this systematic review aimed to evaluate the effects of Qigong exercise on cardiovascular risk factors in patients with metabolic syndrome. Objective: Relevant randomized controlled trials were identified to conduct a meta-analysis of the effects of Qigong exercise on patients with metabolic syndrome, and to further explore the overall impact, heterogeneity, and publication bias related to the effects of Qigong exercise on metabolic syndrome. Methods: We searched for RCTs of Qigong exercise in patients with metabolic syndrome from the following databases: Pubmed, Web of Science, The Cochrane Library, Scopus, Embase, Physiotherapy Evidenced Database (PEDro), Google Scholar, Chinese Biomedical Literature Database (CBM), Chinese National Knowledge Infrastructure Database (CNKI), Chinese Science, Wanfang Data, and the VIP database. The search duration was set from the establishment of the database to 16 April 2022. We used the “Bias Risk Assessment” tool recommended by Cochrane Manual 5.0 to assess the methodological quality of the included literature and the R (version 3.6.2) package gemtc to analyze the data. Results: A total of seven RCTs with 486 participants were included in the meta-analysis. The results showed that Qigong exercise had significant effects on waist circumference (standardized mean difference [SMD] = −0.67; 95% CI, −1.16 to −0.17), systolic blood pressure (standardized mean difference = −0.53; 95% CI, −0.78 to −0.28) and triglyceride level (SMD = −0.60; 95% CI, −0.79 to −0.41). Subgroup analyses showed that 6-month Qigong exercise significantly improved diastolic blood pressure (SMD = −1.06; 95% CI, −1.57 to −0.56), high-density lipoprotein cholesterol level (SMD = 1.45; 95% CI, 1.06–1.85), total cholesterol level (SMD = −0.65; 95% CI, −1.04 to −0.27), and body mass index (SMD = −0.97; 95% CI, −1.23 to −0.72). For fasting blood glucose (SMD = −1.12; 95% CI, −1.58 to −0.67), the effect of a 3-month intervention seemed more effective than 6 months of Qigong exercise, but the evidence was insufficient. In addition, Qigong exercise had minimal effects on low-density lipoprotein cholesterol levels (SMD = −1.22; 95% CI, −1.95 to −0.50). Conclusion: Qigong may be an alternative exercise mode to improve cardiovascular risk factors in patients with metabolic syndrome. However, the findings are limited by the number and quality of the included studies, and require validation through more high-quality studies.